Growth, immune responses and intestinal morphology of rainbow trout (Oncorhynchus mykiss) supplemented with commercial probiotics. Issue 1 (July 2015) - Ramos, M.A.; Gonçalves, J.F.M.; Batista, S.; Costas, B.; Pires, M.A.; Rema, P.; Ozório, R.O.A.
Abstract: The influence of two commercial probiotics on the growth, innate immune parameters and intestinal morphology of rainbow trout (O ncorhynchus mykiss ) juveniles (initial weight: 16.4 ± 0.4 g) was evaluated. Two probiotic types: A, multi-species ( Bacillus sp., Pedicoccus sp., Enterococcus sp., Lactobacillus sp.) and B, mono-species ( Pediococcus acidilactici ) were tested at two levels each (A1 : 1.5 g kg −1, 8.6 × 10 5  CFU g −1 ; A2 : 3 g kg −1, 1.6 × 10 6  CFU g −1 ; B1 : 0.1 g kg −1, 2.6 × 10 4  CFU g −1 ; B2 : 0.2 g kg −1, 7.2 × 10 4  CFU g −1 ) versus an unsupplemented diet (C). Diets were distributed to sextuplicate tanks, three times a day to visual satiation for 8 weeks. Growth performance and immune responses (plasma lysozyme, ACH50, peroxidase and head kidney respiratory burst) were determined at 4 and 8 weeks of feeding. Body composition and intestine morphology were determined at the end of the feeding trial. At 8 weeks, the lower dose of multi-species probiotic (A1 ) improved growth rate, while both probiotic types improved feed conversion rate compared to the control animals, at the lower dose of multi-species (A1 ) and at the higher dose of mono-species (B2 ) probiotics. Body composition did not vary between treatments. At 4 weeks, ACH50 activity was significantly higher in fish fed higher dose of B probiotic (B2, 123.7 ± 50.6 vs 44.1 ± 7.7 U.ml -1 in control). At 8 weeks, lysozyme activity was higher in fish fed A1 (13.1 ± 5.2 μg ml −1 ) diet compared to fish fed control diet (7.8 ± 1 μg ml −1 ). Plasma peroxidase and head-kidney respiratory burst did not differ among the dietary treatments. Villi length and integrity and goblet cell counting of a cross section of the anterior intestine were not significantly different between groups. Results suggest benefits in zootechnical performance and immune humoral responses using both probiotic types, in a dose dependent manner, without apparent alterations in intestinal morphology. Highlights: Two commercial probiotics were studied in rainbow trout. Both probiotics altered the innate immune responses. Both probiotics improved growth performance after 8 weeks of treatment.